HOMOLOGY MODELING OF MTNR1B AND INSILICO STRUCTURE ACTIVITY RELATIONSHIP STUDY OF MELATONIN ANALOGS FOR THERAPEUTIC APPLICATION IN INSOMNIA AND INSOMNIA RELATED DIABETES. - PRAMODKUMAR P. GUPTA; VISHAKHA NANAVATY; PRANAV SHAH (International Journal of Pharma and Bio Sciences, 2013)
Melatonin is a circulating hormone that is primarily released from the pineal gland and performs a circadian rhythm in human and plays a vital role in insomnia and diabetes. In order to search promising MTNR1B homolog inhibitors, an in-silico study is carried out. Since there is no reported MTNR1B crystal structural data, three dimensional structure of MTNR1B was modeled based on crystal structure of the Mos1 mariner (PDB: 3HOT_A) and validated using PROCHECK, Ramchandran plot and energy optimization techniques. Further implementing the Insilico molecular modeling and interaction study approaches were performed with 6 different inhibitors including melatonin and reference molecule as a Ramelteon with 5 different cavities detected by MVD where Cavity 2 resulted to a least and favorable energy among all. Melatonin with acetyl side chain extended with butyryl which followed Lipinski rule of five, and a combinatorial library of 177 analogs are designed. After several docking study and Lipinski screening, successively 3 melatonin analogs are designed and screened, which may have a better therapeutic application to the melatonin.